PENGARUH MOTIVASI BELAJAR DAN GAYA BELAJAR TERHADAP PRESTASI BELAJAR AKUNTANSI SISWA KELAS X AKUNTANSI SMK NEGERI 1 SOOKO MOJOKERTO - NOVI PUJI SRI LESTARI (Jurnal Pendidikan Akuntansi (JPAK), 2013)
Learning achievement is influenced by several factors: internal factors and external factors. Internal factors are considered have an important role and influence on student achievement is student motivation and learning styles. But the truth of this argument still needs to be proven through research to obtain a more accurate answer. This research aims to know how student motivation and learning styles aither partially or simultaneously influence student achievement accounting class X Accounting at SMK Negeri 1 Sooko Mojokerto. This research is descriptive quantitative research with engineering documentation and data collection using questionnaires. Data analysis techniques using multiple linear regression analysis using SPSS 16 for windows that have previously been tested classical assumptions. Based on the results of the data analysis, obtained thitung for motivation of 3.801 with a significance level of 0.000 and 3.510 with the learning style of significance level of 0.001. And obtained Fhitung at 37.608 with significance 0.000. In addition to the value of t and F, obtained also the value of R square of 0.381, meaning that 38.1% of student achievement is affected learning motivation and learning styles, while the remaining 61.9% is influenced by other variables beyond the variables used in this study. These results indicate that there is a significant influence of learning motivation and learning styles either partially or simultaneously towards achievement accounting class X Accounting student at SMK Negeri 1 Sooko Mojokerto. Kata kunci : Motivasi belajar, gaya belajar, prestasi belajar siswa